2022
DOI: 10.3390/ijerph191710952
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorders as a Possible Moderator of the Effects of Relational Interventions in Short-Term Psychoanalytic Psychotherapy with Depressed Adolescents

Abstract: A significant proportion of adolescents suffering from major depressive disorder (MDD) are likely to have a co-morbid personality disorder (PD). Short-term psychoanalytic psychotherapy (STPP) was found to be one treatment of choice for adolescents suffering from MDD. Background: The first experimental study of transference work-in teenagers (FEST-IT) demonstrated the efficaciousness of transference work in STPP with adolescents suffering from MDD. The usefulness of STPP may be enhanced by exploring possible mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…It has been argued that women with a lifelong pattern of poor object relations might especially profit from transference work to respond well to STPP [ 58 ]. In line with this, it seems that adolescents with cluster B personality disorder symptoms also do better with transference work than without [ 59 ]. The APQ interaction structure Working with low mentalization indicated that Sonja struggled with mentalising herself and others.…”
Section: Discussionmentioning
confidence: 79%
“…It has been argued that women with a lifelong pattern of poor object relations might especially profit from transference work to respond well to STPP [ 58 ]. In line with this, it seems that adolescents with cluster B personality disorder symptoms also do better with transference work than without [ 59 ]. The APQ interaction structure Working with low mentalization indicated that Sonja struggled with mentalising herself and others.…”
Section: Discussionmentioning
confidence: 79%